За състоянието на категорията бъдеще време в славянските езици - Savova, Dimka (Zeszyty Cyrylo-Metodiańskie, 2018)
On the Category of Future Tense in the Slavic Languages. A review of: Vojvodic, Dojcil. Issues of Future Tense Development and Its Grammaticalization in Slavic Languages (with Special Overview of Its Status in Serbian, Russian and Polish). Second, revised and expanded edition. Ruse: Leni-An, 2014, 196 pp. ISBN 978-619-7058-31-4. [In Serbian: Војводић, Доjчил. Проблематика развоја футура и његове граматикализације у словенским језицима (с посебним освртом на ситуациjу у српском, руском и пољском). Второ, ревизирано и допълнено издание. Русе: Лени-Ан, 2014, 196 стр.]